The Interpretation of Article 127 of Law Number 35 of 2009 on Narcotics in Addressing Drug Abuse through Restorative Justice - Wardika, Made; Harun, Rina Rohayu; Jiwantara, Firzhal Arzhi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Narcotics crime refers to a range of illegal activities involving the distribution, purchase, sale, possession, and abuse of drugs without proper authorisation. These activities cause harm to both the broader community and the individuals involved. Restorative Justice has emerged as a response. Its primary focus is to resolve cases involving drug abusers who are addicted to narcotics. In addition to Restorative Justice, there is an alternative for rehabilitating narcotics abusers through the involvement of police investigators, the prosecutor's office, or decisions made by judges. The purpose of this study is to analyse the relationship between the interpretation and execution of Article 127 of Law No. 35 on Narcotics and Restorative Justice, based on literal interpretation. Based on the analyses, the enforcement of Article 127 of Law No. 35 of 2009 on Narcotics, which focuses on Restorative Justice, has been supported by multiple regulations. However, the law's implementation has not aligned with expected standards and legislation, leading to ambiguity in Article 112 and Article 127. This ambiguity creates opportunities for unscrupulous law enforcement to make illicit gains, increasing the incidence of drug-related offenses. The author proposes an immediate revision of Law No. 35 of 2009 concerning Narcotics due to the ambiguity in the law's article parts and the current legal framework's inability to effectively curb opioid misuse.